The extent to which travel and tourism companies adopt the marketing intelligence system: A field study on a sample of general maagers of private sector companies in the city of Benghazi - عبد الرحمن عيسى الحاسي صالح (Dirasat in Economics and Business, 2024)
This study aimed to identify the extent to which travel and tourism companies have adopted the marketing intelligence system and its dimensions (customer understanding, product intelligence, competitor intelligence, market understanding) from the point of view of their managers, and then to reveal differences in the extent to which these companies have adopted the marketing intelligence system. Based on a number of variables (gender, age, educational level, and years of service). The study used the descriptive approach. To achieve this, a questionnaire tool was developed, and the size of the study population reached (105) members, following the purposive sampling method. The sample size was (83) individuals and the data was analyzed using the statistical software packages for the social sciences (SPSS). The results of the study indicated that travel and tourism companies adopt the tourism marketing intelligence system from the point of view of its managers was (high), but in varying proportions. It was found that marketing intelligence related to the product was most adopted by travel and tourism companies, followed by marketing intelligence related to the market, then marketing intelligence related to the competitor, while marketing intelligence related to the customer in last place. The results of the study also indicated that there are no statistically significant differences in the extent to which travel and tourism companies adopt the marketing intelligence system from the point of view of their managers for all dimensions due to gender, age, educational level, and years of service. Finally, the study presented a set of recommendations that may contribute to strengthening the marketing intelligence system in the travel and tourism companies under study.